Italians Can Resist Everything, Except Flat-Faced Dogs! - Simona Cannas; Clara Palestrini; Sara Boero; Alice Garegnani; Silvia M. Mazzola; Emanuela Prato-Previde; Greta V. Berteselli (Animals)
Brachycephalic dogs remain highly popular despite the well-documented health problems associated with their conformation. The aim of this study was to investigate differences in the bonding between humans and dogs, behavioral characteristics, awareness of clinical breed-related ailments, and purchasing intentions among Italian brachycephalic dog owners (BDOs) and non-brachycephalic dog owners (NBDOs). A questionnaire, including the DORS and C-BARQ scales, was administered to 320 BDOs and 408 NBDOs. Despite the occurrence of breed-related disorders, 81% of BDOs rated their dog’s health status as good to excellent. Most BDOs were aware of the prevalence of these disorders in the broader brachycephalic dog population. Character and appearance were the main motivations for choosing these breeds. Owners’ satisfaction with specific aspects of ownership, such as veterinary costs and behavior, generally met expectations. Mean scores of perceived emotional closeness (PEC) and dog–owner interaction (DOI) were significantly higher among BDOs compared to NBDOs, while the perceived cost (PC) mean score was higher among NBDOs. The C-BARQ scores for trainability, excitability, and separation-related behaviors were significantly higher in BDOs than in NBDOs. Despite the growing awareness of health issues, the popularity of brachycephalic breeds persists. Scientific evidence may support a revision of brachycephalic breed standards, prioritizing animal welfare while preserving desirable aesthetic traits, promoting more ethical breeding.